WORD-FORMING SUFFIXES OF ENGLISH FRONTIER DEFENCE NOUN TERMS: PHONOLOGICAL AND SEMANTIC FEATURES - Yesypenko, Nadia; Yankovets, Olena (Науковий вісник ХДУ Серія Германістика та міжкультурна комунікація, 2020)
Each part of speech is characterized by a specific set of affixes (suffixes and prefixes) that are used to form new words. Nominal terminological units are not an exception. The English frontier terms vocabulary is characterized by a considerable number of nominal lexemes. The coining of English frontier defence terms occurs according to standardized rules of English word formation. Terms containing no affixes are called primitives. Terms formed by adding a prefix, a suffix, or a prefix and a suffix are called derivatives. English frontier defence terms are characterized by the productive affixal way of word formation. Affixal method is a morphological way of word-formation. One of the most productive ways of noun-terms formation is the suffixal method (the prefixal method and the prefixal-suffixal method are less productive ones). In our article the phonological and semantic aspect of the suffixal way of word formation of English terms of the frontier sphere are considered. From the phonetic point of view, all suffixes are divided into those that cause a change in the stress of the derived lexeme, and those where the suffix has no effect on the stress. From the semantic point of view, a suffix has a semantic function and shows the belonging of a derivative to a specific lexical and semantic group. The meanings of a derived noun-term are the result of the interaction between the meaning of the suffix and that of the root. The semantic network of the nominal suffixes that form noun-terms of the frontier defence includes three multifaceted domains: ACTIVITY/ PROCESS, CHARACTERIZATION and AGENTHOOD within which the meanings of suffixes can be understood. Domains house noun-forming suffixes under one roof and single out their individual roles. The meaning of a suffix consists of the way it represents the facet within the domain. Each domain encompasses its own set of suffixes
Keywords: terminology; word-building; nominal suffix; semantic domain; productivity; stress